A study on entrepreneurial innovation among entities in Singapore - Easwaramoorthy Rangaswamy; Nishad Nawaz; Sirajudeen Bin Syed Mohamed; Gemini Velleringatt Joy (Journal of Innovation and Entrepreneurship, 2024)
The present study aimed to study the entrepreneurial innovation among entities in Singapore. It evaluated the various obstacles that affect entrepreneurial innovation within entities. Further, it has also analysed the various elements that are crucial to overcome the obstacles that affect entrepreneurial innovation within entities. Various factors related to various sources of information fostering innovation activities in an organization were also studied. Difference between the product innovation and process innovation was studied. Furthermore, organizational innovation and marketing innovation were also studied. Lastly, organizational innovation's degree of observed effect in the organization was also studied. Cross-sectional analysis using realism as epistemological view was undertaken in this study. Deductive research approach along with web-based survey using descriptive research design is the research methods followed in this study. Tools for results' analysis include descriptive analysis, Q-Q plots, KMO and Bartlett's test, factor analysis and Chi-square tests. The study concluded that enterprises need to work aggressively in the new product development, market opportunities, organization capabilities to ensure that the organizations grow. It is highlighted that process innovation and product innovation have effects on the economic performance of the organization. It does flag that the market innovations are linked with the ways the enterprises change, evolve and develop their fundamental capabilities, which are part of the organizational innovations. Also, the study showed that organizational innovation has greatly helped to improve the quality of the goods or services and reduced costs per unit output. The reduced time to respond to customer or supplier needs and improved employee satisfaction and/or reduced rates of employee turnover is also seen as a significant observed effect of entrepreneurial innovation. Managerial and theoretical implications along with Ideas for future research is also provided.
Keywords: 650; Entrepreneurial innovation; Innovation; Marketing innovation; Organizational innovation; Process innovation; Product innovation